Respostas

A melhor resposta!
2014-03-24T16:32:24-03:00
6) Sabe-se que cos (a - b) = cos a.cos b + sen a. sen b

Logo, cos (x - π/3) = cos x. cos π/3 + sen x. sen π/3 = cos x. 1/2 + sen x. √3/2

Se sen x = 1/4 ⇒ cos x = +/-\sqrt{1 - sen^{2}x } = +/-\sqrt{1 - ( \frac{1}{4} )^{2} } =+/-\sqrt{1 - \frac{1}{16} }=+/-\sqrt{\frac{15}{16} }=+/- \frac{ \sqrt{15} }{4} ⇒ escolhe-se o valor negativo, pois π/2 < x < π

cos(x- \frac{ \pi }{3} )= (-\frac{ \sqrt{15} }{4}) . \frac{1}{2} + \frac{1}{4} . \frac{ \sqrt{3} }{2} =-\frac{ \sqrt{3}. \sqrt{5} }{8} + \frac{ \sqrt{3} }{8} = \frac{ \sqrt{3}.( 1-\sqrt{5}) }{8}

=============================================================

7)  sen a =  \frac{2}{3} cos a =  +/-\sqrt{1- sen^{2}a } =+/-\sqrt{1-  ( \frac{2}{3} )^{2}  }=+/-\sqrt{1-  \frac{4}{9}}==+/-\sqrt{\frac{5}{9}}=+/- \frac{ \sqrt{5} }{3} ⇒ escolhe-se o valor positivo, pois 0 < a < π/2

cos b = \frac{ \sqrt{3} }{2} sen b = +/-\sqrt{1- cos^{2}b } =+/-\sqrt{1- ( \frac{ \sqrt{3} }{2} )^{2} }=+/-\sqrt{1- \frac{3}{4}}=+/-\sqrt{\frac{1}{4}}=+/- \frac{1}{2} ⇒ escolhe-se o valor positivo, pois 0 < a < π/2

sen (a + b) = sen a. cos b + cos a. sen b =  \frac{2}{3} . \frac{ \sqrt{3} }{2} + \frac{ \sqrt{5} }{3} . \frac{1}{2} =  \frac{2 \sqrt{3}+ \sqrt{5}  }{6}
1 5 1